Optimization of In vitro Sterilization and Initial Cultivation Methods for Local Garlic (Allium sativum L.) Varieties : - Matai, Z.; Zhantasov, S.; Ibragimova, G. (Fundamental and Experimental Biology, 2026)
This article explores the optimization of sterilization and initial cultivation methods for local garlic (Allium sativum L.) varieties under in vitro conditions. Due to the biological characteristics of garlic, which rarely produces viable seeds, and the limited efficiency of conventional vegetative propagation methods, planting material is often susceptible to the accumulation of viral and fungal infections. Therefore, the use of biotechnological approaches represents an important direction for improving plant health and producing high-quality, uniform planting material. In this study, explants of the “Arman”, “Zailiysky”, and “Dungansky” varieties were cultured on Murashige and Skoog (MS) nutrient medium. Effective sterilization methods were selected, and optimal conditions for growth were determined. According to the obtained results, all studied varieties demonstrated good morphogenetic responses and showed a high potential for micropropagation in vitro. This method enables the establishment of an in vitro collection of local garlic varieties and can be applied in agricultural production for obtaining high-quality planting material. Furthermore, this technology ensures biological safety and facilitates the rapid propagation of virus- and fungus-resistant forms of garlic.